Systems thinking approach to human resources development in public health supply chains - Erin, Meier; Andrew, Nelson Brown; Barry, Chovitz; Dominique, Zwinkels; Egharevba, Michael; Bridget, McHenry; Kabatende, Joseph; Ines K. Gege (Emerald, 2024)
Purpose This practice forum paper aims to present a theoretical framework to better develop the required supply chain management (SCM) competencies and the workforce needed for managing public health supply chains. Design/methodology/approach This framework is driven by iterative systems thinking, a deeper consideration of the SCM labor market and a comprehensive mapping of human resource system requirements. The framework centers around three tools. A labor market analysis assesses factors influencing supply of and demand for health SCM workers in a country context. To improve supply of and demand for workers, the SCM Professionalisation Framework provides reference documents to establish health SCM as a recognized profession. The human resources for SCM Theory of Change explains and assesses the conditions required to achieve optimal workforce performance at the organizational level. The Ministry of Health in Rwanda applied these three tools sequentially to assess and improve the supply and performance of its health SCM workforce. Findings The authors describe this framework, how the tools were applied in Rwanda, and early impressions of the results. Practical implications Practitioners can apply this approach to improve SCM competence and promote the attractiveness of health SCM positions by formalizing their professional status. This could lead to a pool of individuals who seek SCM qualifications and, in time, overcome the current shortage of health SCM workers. Employers can apply this approach to structured roles and workforce needs to meet health SCM system requirements. This would lead to a greater demand for and use of appropriately trained personnel. Originality/value This paper presents a novel, iterative, systems-thinking approach to develop human resources in public health supply chains. Rwanda is the first country to apply all three tools using this framework.